The effect of internal waves on sound propagation parallel to the internal wave crests - Duncan, Alec; Parnum, Iain; MacLeod, R. (2019)
© 2019 Australian Acoustical Society Annual Conference, AAS 2018. All rights reserved. This study investigated the likely effects of nonlinear, short period, internal waves, typical of those that occur on Australia's Northwest Shelf, on the propagation of underwater sound. Measured oceanographic data from the Integrated Marine Observing System was used as a basis for fully three-dimensional acoustic propagation modelling. The effect of the passage of a group of nonlinear internal waves on acoustic propagation in a direction parallel to the internal wave crests at a frequency of 7 kHz was examined. The results indicated that changes in incoherent transmission loss at a range of 15 km, during periods of high internal wave activity, could be as much as 30 dB over ten minutes, and have a standard deviation of 9.2 dB over an hour. This was approximately double the standard deviation over a 1-hour period of relatively low internal wave activity. However, the modelling involved some simplifications that may impact on the accuracy of these results, which are discussed.